Associations of cannabis use disorder with cognition, brain structure, and brain function in African Americans. Issue 6 (19th December 2020) - Koenis, Marinka M. G.; Durnez, Joke; Rodrigue, Amanda L.; Mathias, Samuel R.; Alexander‐Bloch, Aaron F.; Barrett, Jennifer A.; Doucet, Gaelle E.; Frangou, Sophia; Knowles, Emma E. M.; Mollon, Josephine; Denbow, Dominique; Aberizk, Katrina; et al.
Abstract: Although previous studies have highlighted associations of cannabis use with cognition and brain morphometry, critical questions remain with regard to the association between cannabis use and brain structural and functional connectivity. In a cross‐sectional community sample of 205 African Americans (age 18–70) we tested for associations of cannabis use disorder (CUD, n = 57) with multi‐domain cognitive measures and structural, diffusion, and resting state brain‐imaging phenotypes. Post hoc model evidence was computed with Bayes factors (BF) and posterior probabilities of association (PPA) to account for multiple testing. General cognitive functioning, verbal intelligence, verbal memory, working memory, and motor speed were lower in the CUD group compared with non‐users ( p < .011; 1.9 < BF < 3, 217). CUD was associated with altered functional connectivity in a network comprising the motor‐hand region in the superior parietal gyri and the anterior insula ( p < .04). These differences were not explained by alcohol, other drug use, or education. No associations with CUD were observed in cortical thickness, cortical surface area, subcortical or cerebellar volumes (0.12 < BF < 1.5), or graph‐theoretical metrics of resting state connectivity (PPA < 0.01). In a large sample collected irrespective of cannabis used to minimize recruitment bias, we confirm the literature on poorer cognitive functioning in CUD, and an absence of volumetric brain differences between CUD and non‐CUD. We did not find evidence for or against a disruption of structural connectivity, whereas we did find localized resting state functional dysconnectivity in CUD. There was sufficient proof, however, that organization of functional connectivity as determined via graph metrics does not differ between CUD and non‐user group. Abstract : In a large sample collected irrespective of cannabis used to minimize recruitment bias, we confirm the literature on poorer cognitive functioning in cannabis use disorder (CUD), and an absence of volumetric brain differences between CUD and non‐CUD. A disruption of structural connectivity remains equivocal. We find localized resting state functional dysconnectivity in CUD, and sufficient proof that organization of functional connectivity as determined via graph metrics does not differ between CUD and non‐users.